Stereotypes of the West in El Alamy’s Un Marocain à New York (Philologia, 2021)
This article focuses on cross-cultural perception involving the Orient and the Occident. It attempts to demonstrate how cultural stereotypes are absurd, dwelling on the way the Orientalist discourse implements a number of stereotypes about the Orient. The article goes on to show that the oriental perception of the West may proceed in the same way to construct a discourse elaborated round stereotypes about the West. Based on a reading of a novel by a Moroccan writer, the article raises the question whether it might be legitimate to assume that Orientalism has a counterpart, Occidentalism, a discourse steeped in anti-Western thoughts.
Keywords: Orientalism; Orient; Occidentalism; West; Oriental; Western; Orientalist discourse; stereotypes; post colonialism; ambivalence; irony